Social and political capital in rural Viet Nam - Thomas Markussen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper exploits five waves of the Vietnam Access to Resources Household Survey (VARHS) to investigate issues of social and political capital in rural Viet Nam. I analyse membership of the Communist Party, 'mass organizations' (Farmers' Union, Women's Union, etc.) and other voluntary organizations, trust, and the significance of family ties in economic transactions (e.g. the share of land tenants who are relatives of their landlord). The paper also presents fixed effects regressions exploring the effects of social and political capital on household income. Results indicate positive returns to Communist Party membership, trust and access to informal insurance.
Keywords: D73; H7; O12; O53; P16; 330; social capital; political capital; trust; family ties; household income; Viet Nam